Messages from the Genome. - Cody, Arthur B. (Commentary, 2000)
Comments on the debate over the issue whether the genome possess both sufficient genetic information and sufficient power to make an organism. Scientific description of the genome; Information about the Human Genome Project; Metaphors to capture the constructive power of the genome.